Social Work Services for Children With Autism and Their Families in Vietnam - Hai Trung Nguyễn (Asian Social Work Journal, 2020)
In Vietnam, autism has only been known for more than 10 years, but it has quickly become a burden not only for family with autistic children, but also a burden for the whole society. Although there is no official published data, the number of children diagnosed and treated with autism at public health facilities has increased from 2000 to the present, higher than the previous year. The models of care, intervention, support for autistic children and their families in the world are taking a holistic approach and emphasizing the role of social work services because these services cover from internal Prevention, Intervention, Recovery and Development for children with autism and their families. For Vietnam, social work for a young job is only officially recognized as a job through the project No: 32/2010/QD-TTg "Development of social work careers in the period of 2010 - 2020”. In current conditions in Vietnam, social work services in the community are still new and in the process of development. Research results show that facilities are making efforts in providing social work services to autistic children and their families. However, because of many different reasons, these services have not really developed in a professional way. This limits the effectiveness of interventions with autistic children and their families in the current context in Vietnam.